New and Facile Synthesis of Aminobicyclo[2.2.1]heptane-2-carboxylic Acids - Kim, Taek-Soo; Seo, Seung-Yong; Shin, Dongyun (Synlett, 2015)
A facile approach for the stereoselective synthesis of a- and b-2-aminobicyclo[2.2.1]heptane-2-carboxylic acid is described. Substrate-controlled α-carboxylation of norbonene monoester delivered the asymmetric diester intermediate with high diastereoselectivity (up to 35:1). Sequential chemoselective ester cleavage, Curtius rearrangement, and hydrolysis gave the a- and b-isomers of 2-aminobicyclo[2.2.1]heptane-2-carboxylic acid, respectively.
Keywords: carbocycles; amino acids; bicyclic compounds; diastereoselectivity; carbonylation